How conflicting perspectives lead a history teacher to epistemic, epistemological, moral and temporal switching: a case study of teaching about the holocaust in the Netherlands. Issue 4 (4th July 2021) - Wansink, Bjorn G. J.; Akkerman, Sanne F.; Kennedy, Brianna L.
ABSTRACT: This case study reports on a history teacher in a multicultural classroom in the Netherlands who is confronted with students' conflicting perspectives on a sensitive topic, namely the Holocaust. We have used Dialogical Self Theory in combination with the historical multiperspectivity framework to make sense of the teacher's considerations and instructional responses. Informed by interactions between three inner-voices (i.e. history teacher, caring teacher, and political citizen) and two inner-other voices (i.e. Jews as victims and 'the resistant boys'), the teacher switches from a temporal focus on the past to a temporal focus on the present. The epistemic, epistemological, and moral consequences of this temporal switching are discussed.